1990
DOI: 10.1111/j.1432-1033.1990.tb19169.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional properties of phosphorylated elongation factor 2

Abstract: The effect of phosphorylation on the functional activity of eukaryotic elongation factor 2 (eEF-2) was studied using a purified phosphorylated factor. The modified factor was unable to stimulate protein synthesis in an eEF-2-dependent rabbit reticulocyte lysate. The functional alteration was further analyzed by measuring the effects of phosphorylation on the ability of the factor to catalyse the ribosome-dependent hydrolysis of GTP. Kinetic analysis showed that both phosphorylated and unmodified factor was abl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
201
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 252 publications
(209 citation statements)
references
References 39 publications
(13 reference statements)
8
201
0
Order By: Relevance
“…If the interaction of the phosphorylated factor were tighter than that of non-phosphorylated eEF-2 it could then exert a dominant inhibitory effect by blocking the binding, and thus the action, of nonphosphorylated eEF-2. However, as mentioned above, Nyg h d and co-workers have reported that phosphorylated eEF-2 (apparently mono-phosphorylated) failed to bind efficiently to ribosomes [19]. This was due to a 10-100-fold decrease in affinity for ribosomes in complexes resembling the pretranslocational complexes which arise in elongation.…”
Section: Discussionmentioning
confidence: 93%
“…If the interaction of the phosphorylated factor were tighter than that of non-phosphorylated eEF-2 it could then exert a dominant inhibitory effect by blocking the binding, and thus the action, of nonphosphorylated eEF-2. However, as mentioned above, Nyg h d and co-workers have reported that phosphorylated eEF-2 (apparently mono-phosphorylated) failed to bind efficiently to ribosomes [19]. This was due to a 10-100-fold decrease in affinity for ribosomes in complexes resembling the pretranslocational complexes which arise in elongation.…”
Section: Discussionmentioning
confidence: 93%
“…[22][23][24]49 We therefore asked whether eEF-2K is necessary for the full downregulation of translation observed during ER stress. We treated wild-type and eEF-2K À/À MEFs with Tg to induce rapid, synchronous ER stress and then metabolically labeled newly synthesized proteins with radioactive amino acids.…”
Section: Resultsmentioning
confidence: 99%
“…It is phosphorylated on threonine residues by a specific eEF-2 kinase, (previously termed Caa+/calmodulin.dependent protein kinase III [3,4]) and its phosphorylation is increased in intact ceils in response to stimuli which increase intracellular Ca z÷'ion concentrations [6][7][8][9][10][11][12][13]. Phosphorylation of the endogenous eEF-2 impairs the translation of mRNA in the reticulocyte lysate celt-free system [5] and several other lines of evidence show that phosphorylated eEF-2 is inactive, or has only low activity [3,4,14,15].…”
Section: Introductionmentioning
confidence: 99%